(untitled) (Academicia Globe: Inderscience Research, 2022)
The peculiarities of the science of notation and computer programs and its foundations, the problems of scientific methodology, the main directions and methods of modern ethnomusicology are described. In the field of notation and computer programming, students learn to work perfectly with computer programs.